EDUCATIONAL THEORIES OF SIR SYED AHMAD KHAN - Dr Bismina Siraj; Dr. Robina Rashid; Dr. Raheela khurshid; Dr Zeenat bibi; Nabila shaheen (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Sir Syed Ahmad Khan is one of those leaders who always lamented that his nation had lagged far behind other nations in enlightenment and education. This is the reason why he tried his best to make Muslims aware of the importance of education and in this way they will also get education and become respectable in the eyes of other nations. Sir Syed’s national ideology also influenced his educational plans. That is why his education policy was appreciated in the background of national education.